Does engaging in global market orientation strategy affect HEIs' performance? The mediating roles of intellectual capital readiness and open innovation - Bambang Tjahjadi; Noorlailie Soewarno; Johnny Jermias; Hariyati Hariyati; Atika Fairuzi; Dewi Nabilah Anwar (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
This study aims to examine the effect of global market orientation strategy on the performance of Indonesian Higher Education Institutions. Furthermore, it investigates whether this relationship is mediated by intellectual capital readiness and open innovation. This is a quantitative study employing a multi-mediation research model conceptualizing the relationship among the five constructs. This study employs a resource-based view to explain the relationships among constructs and partial least squares-structural equation modeling to test the hypotheses studied. A sample of 119 schools/faculties, derived from the 50 best state and private institutions in Indonesia and based on the Webometrics 2021, was used. This research reveals the following main results. First, intellectual capital readiness fully mediates the influence of global market orientation strategy on the institutions' performances. Second, open innovation does not mediate the effect of global market orientation strategy on institutions' performances. This study is the first attempt to understand how global market orientation strategy enhances institutions' performances via intellectual capital readiness and open innovation. This study reveals the insignificant effect of open innovation on performance. Thus, the main implication of these findings is that institutions need to downstream their innovations to the community for future performance and communities' benefits. The applied execution does matter in the open innovation-institution performance relationship.
Keywords: 650; open innovation; education; global market orientation strategy; higher education institutions' performance; intellectual capital readiness